A modified spectrophotometric method for selective determination of trace urea: application in the production process of ultrapure water. Issue 3 (1st September 2022) - Jiang, Shilong; Xiong, Jianglei; Cheng, Song; Cao, Jiashun; Yuan, Runbo
Abstract: Conventional spectrophotometric methods were unable to accurately detect urea concentrations below 100 μg/L. A modified spectrophotometric method was developed to determine the trace urea in the ultrapure water (UPW) production process of the semiconductor manufacturing industry. This method was optimized based on the dosage of chemical agents, length of the optical path, and mode of the water bath. Metal ions were added to promote the stability of the chromogenic system. A calibration graph was observed with ideal linearity in the range of 0.8–100 μg/L. The detection and quantification limits of urea were 0.24 and 0.80 μg/L, respectively. The distribution of urea in raw water for the UPW production process was observed and the urea in tap water was 10–20 μg/L. The urea of municipal reclaimed water was 24–40 μg/L, which was twice that of industrial reclaimed water at 10–18 μg/L. The total removal rate of urea by the UPW production process was 50–70%. Reverse osmosis membranes played a critical role in the removal of urea (over 30%). The urea in the final UPW produced from tap water was approximately 4.1 μg/L, which creates a potential risk of excessive total organic carbon. HIGHLIGHTS: A spectrophotometric method for the determination of trace urea during ultrapure production process was first established. Stability of the absorbance in the color reaction was increased by doping metal ions. The urea concentration of municipal reclaimed water was twice that of industrial reclaimed water. The urea removal efficiencies in each unit of the ultrapure water production process were explored. Graphical Abstract